A kind of anti-corrosion cable and its processing technology
By adding modified graphene oxide and inorganic flame retardant to the outer sheath layer of cable EVA material, the problem of corrosion of cables in acidic or alkaline environments is solved, and higher corrosion resistance and flame retardant and fire-resistant properties are achieved, and suitable for harsh environments and high and low temperature conditions.
Patent Information
- Application Number
- CN202210774441.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-01
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-07-01
AI Technical Summary
Existing cables are prone to corrosion in acidic or alkaline environments, resulting in reduced transmission effects and stability effects.
Modified graphene oxide and inorganic flame retardant are added to the outer sheath layer of EVA material, and a composite coupling agent is combined to form a stable inorganic-organic hybrid system to improve corrosion resistance and flame retardant fire resistance.
It significantly improves the corrosion resistance and flame retardant performance of the cable, making it suitable for harsh environments and high and low temperature conditions, extending the service life of the cable.
Smart Images

Figure BDA0003726151690000031 
Figure BDA0003726151690000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cables, and in particular relates to an anti-corrosion cable and a processing technology thereof. Background Art
[0002] Wires and cables are widely used in various fields as a transmission medium for electric energy and information. However, the working environment of cables is usually a relatively harsh working environment. Sometimes they work in an acidic or alkaline environment. Such a working environment often requires cables to have good corrosion resistance. However, many cables currently have weak corrosion resistance. They often corrode after being used in an acidic or alkaline environment for a period of time, which seriously affects the transmission effect of the cables. The cables often lose signals during transmission, which greatly reduces the use effect of the cables and affects the stability of the cable transmission.
[0003] In order to improve the protection effect of the cable, an outer protective sheath is usually set on the outside of the cable. The commonly used cable sheath is rubber or polyethylene material. The rubber sheath has good elasticity, but poor weather resistance and is prone to aging and cracking. The polyethylene sheath material is brittle, with poor wear resistance and toughness, and cannot play a good role in protecting the cable. Ethylene-vinyl acetate copolymer (EVA) is used as the outer sheath layer material because of its corrosion resistance, good flexibility, good low temperature resistance, resistance to environmental stress cracking, and good insulation. However, although EVA itself has certain corrosion resistance, its corrosion resistance is still difficult to meet the use requirements in more severe environments, and its flame retardant and fireproof performance is weak, making it difficult to use in high temperature environments. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide an anti-corrosion cable and a processing technology thereof.
[0005] In order to improve the corrosion resistance of EVA, the present invention adds modified graphene oxide to the sheath layer. Graphene oxide is grafted with organic molecular chains on the surface through chemical bonding, which can improve its compatibility with the matrix and promote uniform dispersion. It has a very high force with the EVA matrix to form a stable inorganic-organic hybrid system, further improving the corrosion resistance and thermal stability. In order to improve the flame retardant and fireproof properties of EVA, an inorganic flame retardant is added to the sheath layer, and a coupling agent is compounded to effectively improve the flame retardant and fireproof properties of EVA. The outer sheath layer obtained by the present invention has extremely high corrosion resistance and excellent flame retardant and fireproof properties, so that the prepared cable can be suitable for places with harsh environments, and can be used under high and low temperature conditions, and has higher applicability.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] An anti-corrosion cable comprises a conductor core, a conductor shielding layer is wrapped around the outside of the conductor core, an insulating rubber layer is wrapped around the outside of the conductor shielding layer, and an outer sheath layer is wrapped around the outside of the insulating rubber layer;
[0008] The outer sheath layer is made of EVA material, and the raw materials of the EVA material include, by weight: 75-85 parts of ethylene-vinyl acetate copolymer (EVA), 0-20 parts of linear low-density polyethylene, 3-4 parts of modified graphene oxide, 12-15 parts of flame retardant, 1.8-2.2 parts of coupling agent, and 0.2-0.3 parts of antioxidant;
[0009] The processing technology of the above-mentioned anti-corrosion cable comprises the following steps:
[0010] The flame retardant and the coupling agent are mixed uniformly in a high-speed mixer, and then ethylene-vinyl acetate copolymer, linear low-density polyethylene, modified graphene oxide and antioxidant are added to the high-speed mixer for blending, and finally the mixed raw materials are extruded through a twin-screw extruder at 190-250° C., cooled, dried, cut and granulated to obtain EVA material;
[0011] The conductor shielding layer and the insulating rubber layer are sequentially coated on the outside of the conductor core, and finally the EVA material is wrapped around the outside of the insulating rubber layer to form an outer sheath layer to obtain an anti-corrosion cable.
[0012] Furthermore, the flame retardant is one or a combination of several of magnesium hydroxide, aluminum hydroxide, zinc borate and antimony oxide in any proportion.
[0013] Furthermore, the coupling agent is a silane coupling agent or an aluminate coupling agent.
[0014] Furthermore, the antioxidant is one of antioxidant 1010, antioxidant 1076, and antioxidant 168, or a mixture of several of them.
[0015] Further, the modified graphene oxide is prepared by the following steps:
[0016] C1. Add 2,2-oxodiethylamine and tetrahydrofuran (THF) into a three-necked flask, then add triethylamine, stir and mix evenly, slowly drip acryloyl chloride into the mixture using a constant pressure dropping funnel under ice bath conditions, react at room temperature for 2 hours after dripping, and after the reaction is completed, wash with saturated brine and saturated NaHCO3 solution in turn, dry with anhydrous magnesium sulfate, and distill under reduced pressure to obtain an intermediate; the amount ratio of 2,2-oxodiethylamine, tetrahydrofuran, triethylamine, and acryloyl chloride is 0.1 mol: 120 mL: 3.7 mL: 0.105 mol;
[0017] The -NH2 on the 2,2-oxydiethylamine molecule reacts with the acyl chloride to generate an amide to obtain an intermediate; by controlling the molar ratio of 2,2-oxydiethylamine to acryloyl chloride to be basically 1:1, there is still an exposed -NH2 on the 2,2-oxydiethylamine molecule that does not participate in the reaction, providing a reaction site for subsequent reactions. The reaction process is as follows:
[0018]
[0019] C2. After mixing graphene oxide with dichloromethane, add a small amount of triethylamine, ultrasonicate for 15 minutes, dissolve the intermediate in dichloromethane to prepare an intermediate solution with a mass fraction of 10%, drip the intermediate solution into the system using a constant pressure dropping funnel at room temperature, raise the temperature to 50°C and react for 90 minutes, filter, wash the filter cake with ethanol and deionized water for 3-4 times in turn, and vacuum dry to obtain modified graphene oxide; the ratio of graphene oxide, dichloromethane, triethylamine and intermediate solution is 1g:90mL:1.8mL:5.6mL;
[0020] The -NH2 contained in the intermediate molecule reacts with the -COOH on the graphene oxide molecule, and an organic molecular chain is grafted on the surface of the graphene oxide to obtain modified graphene oxide;
[0021] The obtained modified graphene oxide molecules are grafted with organic molecular chains, which can improve the hydrophilicity and agglomeration of graphene oxide, thereby improving the compatibility of graphene oxide with the matrix (ethylene-vinyl acetate copolymer), promoting the uniform distribution of graphene oxide in the outer sheath layer, and the flake graphene oxide forces the corrosive medium to be transmitted inward along the curve in the coating through physical barrier effect, extending the migration and diffusion path, thereby greatly delaying the progress of corrosion; in addition, the organic molecular chain grafted with graphene oxide contains multiple amide bonds and -C=C, the amide bonds have high compatibility with the ester group in the ethylene-vinyl acetate copolymer, and -C=C can participate in the subsequent melt polymerization process of the ethylene-vinyl acetate copolymer. Therefore, the graphene oxide has a strong interaction with the matrix, forming a stable inorganic-organic hybrid system, further improving the corrosion resistance and thermal stability, and improving the migration resistance of the graphene oxide, so that it can play a role continuously and stably.
[0022] Beneficial effects of the present invention:
[0023] In order to improve the corrosion resistance of EVA, the present invention adds modified graphene oxide to the sheath layer. The graphene oxide is grafted with organic molecular chains on the surface through chemical bonding, which can improve its compatibility with the matrix and promote uniform dispersion. The uniformly dispersed lamellar graphene oxide plays a physical barrier role and improves the corrosion resistance of the EVA material. The organic molecular chain grafted on the surface of the graphene oxide contains an amide-bonded carbon-carbon double bond, which has a very high force with the EVA matrix, forming a stable inorganic-organic hybrid system, further improving the corrosion resistance and thermal stability.
[0024] In order to improve the flame retardant and fireproof performance of EVA, the present invention adds an inorganic flame retardant to the sheath layer and compounded with a coupling agent. Under the action of the coupling agent, the inorganic flame retardant is well dispersed in the EVA matrix, effectively improving the flame retardant and fireproof performance of EVA.
[0025] The outer sheath layer obtained by the present invention has extremely high corrosion resistance and excellent flame retardant and fireproof properties, so that the prepared cable can be used in places with harsh environments and can be used under high and low temperature conditions, and has higher applicability. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] Preparation of modified graphene oxide:
[0029] C1. Add 0.1 mol of 2,2-oxodiethylamine and 120 mL of tetrahydrofuran into a three-necked flask, then add 3.7 mL of triethylamine, stir and mix evenly, slowly drop 0.105 mol of acryloyl chloride into the mixture using a constant pressure dropping funnel under ice bath conditions, react at room temperature for 2 h after the reaction is completed, wash with saturated brine and saturated NaHCO3 solution in turn, dry over anhydrous magnesium sulfate, and distill under reduced pressure to obtain an intermediate;
[0030] C2. After mixing 1 g of graphene oxide with 90 mL of dichloromethane, add 1.8 mL of triethylamine, and ultrasonicate for 15 min. Dissolve the intermediate in dichloromethane to prepare an intermediate solution with a mass fraction of 10%. Use a constant pressure dropping funnel to drop 5.6 mL of the intermediate solution into the system at room temperature, raise the temperature to 50 ° C and react for 90 min. Filter with suction, wash the filter cake with ethanol and deionized water three times in turn, and vacuum dry to obtain modified graphene oxide.
[0031] Example 2
[0032] Preparation of modified graphene oxide:
[0033] C1. Add 0.2 mol of 2,2-oxodiethylamine and 240 mL of tetrahydrofuran into a three-necked flask, then add 7.4 mL of triethylamine, stir and mix evenly, and slowly drop 0.105 mol of acryloyl chloride into the mixture using a constant pressure dropping funnel under ice bath conditions. After the drop is complete, react at room temperature for 2 h. After the reaction is completed, wash with saturated brine and saturated NaHCO3 solution in turn, dry over anhydrous magnesium sulfate, and distill under reduced pressure to obtain an intermediate;
[0034] C2. After mixing 2 g of graphene oxide with 180 mL of dichloromethane, add 3.6 mL of triethylamine, and ultrasonicate for 15 min. Dissolve the intermediate in dichloromethane to prepare an intermediate solution with a mass fraction of 10%. Use a constant pressure dropping funnel to drop 11.2 mL of the intermediate solution into the system at room temperature, raise the temperature to 50 ° C and react for 90 min. Filter with suction, wash the filter cake with ethanol and deionized water four times in turn, and vacuum dry to obtain modified graphene oxide.
[0035] Example 3
[0036] Preparation of EVA material:
[0037] The raw materials of the EVA material include: 75 g of ethylene-vinyl acetate copolymer (EVA), 0 g of linear low-density polyethylene, 3 g of modified graphene oxide prepared in Example 1, 12 g of magnesium hydroxide, 1.8 g of silane coupling agent KH570, and 0.2 g of antioxidant 1010;
[0038] The magnesium hydroxide and the silane coupling agent KH570 are mixed uniformly in a high-speed mixer, and then the ethylene-vinyl acetate copolymer, the modified graphene oxide and the antioxidant 1010 are added into the high-speed mixer for blending. Finally, the uniformly mixed raw materials are extruded through a twin-screw extruder at 190° C., cooled, dried, cut and granulated to obtain the EVA material.
[0039] Example 4
[0040] Preparation of EVA material:
[0041] The raw materials of the EVA material include: 80 g of ethylene-vinyl acetate copolymer (EVA), 10 g of linear low-density polyethylene, 3-4 g of modified graphene oxide obtained in Example 2, 13.5 g of aluminum hydroxide, 2.0 g of silane coupling agent KH550, and 0.25 g of antioxidant 1076;
[0042] Aluminum hydroxide and silane coupling agent KH550 are mixed evenly in a high-speed mixer, and then ethylene-vinyl acetate copolymer, linear low-density polyethylene, modified graphene oxide and antioxidant 1076 are added to the high-speed mixer for blending. Finally, the mixed raw materials are extruded through a twin-screw extruder at 225° C., cooled, dried, cut and granulated to obtain EVA material.
[0043] Example 5
[0044] Preparation of EVA material:
[0045] The raw materials of the EVA material include: 85 g of ethylene-vinyl acetate copolymer (EVA), 20 g of linear low-density polyethylene, 4 g of modified graphene oxide obtained in Example 1, 15 g of zinc borate, 1092.2 g of titanate coupling agent, and 1680.3 g of antioxidant;
[0046] Zinc borate and titanate coupling agent 109 are mixed uniformly in a high-speed mixer, and then ethylene-vinyl acetate copolymer, linear low-density polyethylene, modified graphene oxide and antioxidant 168 are added to the high-speed mixer for blending. Finally, the uniformly mixed raw materials are extruded through a twin-screw extruder at 250° C., cooled, dried, cut and granulated to obtain EVA material.
[0047] Comparative Example
[0048] The modified graphene oxide in Example 3 was replaced with ordinary graphene oxide, and the other raw materials and preparation process remained unchanged.
[0049] The EVA materials obtained in Examples 3-5 and the comparative example were pressed into sheets on a flat vulcanizer at 150° C. and a pressure of 10 MPa for 5 min, and their tensile strength and elongation at break were tested using a UT2080 electronic tensile testing machine; the oxygen index of the EVA material was tested according to GB / T 2406-2009;
[0050] The corrosion resistance test of the samples was conducted in a simulated acidic environment. The specific method is as follows: using a salt spray water spray test machine, acetic acid was added to the brine containing 5% sodium chloride to reduce the pH value to 3.1-3.3, and the spray device was used for continuous spraying to allow the salt spray to settle on the sample to be tested. After a certain period of time, the surface corrosion state was observed. The temperature of the test chamber was set at 34-36°C, the humidity was greater than 85%, and the mist drop was set at 2mL / h;
[0051] The measured results are shown in the following table:
[0052]
[0053] It can be seen from the data in the above table that the EVA material prepared by the present invention has higher tensile strength and elongation at break, indicating that the EVA material has mechanical properties that meet the requirements; the oxygen index of the EVA material prepared by the present invention reaches more than 31.0%, indicating that the EVA material has higher flame retardant and fireproof properties; the prepared EVA material does not show corrosion in acidic salt spray for more than 48 hours, indicating that the EVA material has higher corrosion resistance; combined with the data of the comparative example, it can be seen that after modification, graphene oxide can not only improve the corrosion resistance, but also affect the mechanical properties.
[0054] Example 6
[0055] The conductor shielding layer and the insulating rubber layer are sequentially coated on the outside of the conductor core, and finally the EVA material prepared in Example 3 is wrapped around the outside of the insulating rubber layer to form an outer sheath layer, thereby obtaining an anti-corrosion cable.
[0056] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0057] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. An anti-corrosion cable, comprising a conductor core, a conductor shielding layer wrapped around the outside of the conductor core, an insulating rubber layer wrapped around the outside of the conductor shielding layer, and an outer sheath layer wrapped around the outside of the insulating rubber layer, characterized in that: The outer sheath layer is made of EVA material, and the raw materials of the EVA material include, by weight: 75-85 parts of ethylene-vinyl acetate copolymer, 0-20 parts of linear low-density polyethylene, 3-4 parts of modified graphene oxide, 12-15 parts of flame retardant, 1.8-2.2 parts of coupling agent, and 0.2-0.3 parts of antioxidant; Wherein, the modified graphene oxide is prepared by the following steps: C1. Add 2,2-oxodiethylamine and tetrahydrofuran into a three-necked flask, then add triethylamine, stir and mix evenly, slowly drip acryloyl chloride into the mixture using a constant pressure dropping funnel under ice bath conditions, and react at room temperature for 2 hours after the reaction is completed. After the reaction is completed, wash with saturated brine and saturated NaHCO3 solution in turn, dry with anhydrous magnesium sulfate, and distill under reduced pressure to obtain an intermediate; C2. After mixing graphene oxide with dichloromethane, add a small amount of triethylamine, ultrasonicate for 15 minutes, dissolve the intermediate in dichloromethane to prepare an intermediate solution with a mass fraction of 10%, drip the intermediate solution into the system using a constant pressure dropping funnel at room temperature, increase the temperature to 50°C and react for 90 minutes, filter, wash the filter cake with ethanol and deionized water for 3-4 times in turn, and vacuum dry to obtain modified graphene oxide.
2. The anti-corrosion cable according to claim 1, characterized in that: The flame retardant is one or a combination of several of magnesium hydroxide, aluminum hydroxide, zinc borate and antimony oxide in any proportion.
3. The anti-corrosion cable according to claim 1, characterized in that: The coupling agent is a silane coupling agent or an aluminate coupling agent.
4. The anti-corrosion cable according to claim 1, characterized in that: The antioxidant is one of antioxidant 1010, antioxidant 1076, and antioxidant 168, or a mixture of several of them.
5. The anti-corrosion cable according to claim 1, characterized in that: In step C1, the usage ratio of 2,2-oxodiethylamine, tetrahydrofuran, triethylamine and acryloyl chloride is 0.1 mol:120 mL:3.7 mL:0.105 mol.
6. The anti-corrosion cable according to claim 1, characterized in that: In step C2, the ratio of the amount of graphene oxide, dichloromethane, triethylamine and the intermediate solution is 1 g:90 mL:1.8 mL:5.6 mL.
7. The processing technology of the anti-corrosion cable according to claim 1 is characterized in that: The steps include: The flame retardant and the coupling agent are mixed uniformly in a high-speed mixer, and then ethylene-vinyl acetate copolymer, linear low-density polyethylene, modified graphene oxide and antioxidant are added to the high-speed mixer for blending, and finally the mixed raw materials are extruded through a twin-screw extruder at 190-250° C., cooled, dried, cut and granulated to obtain EVA material; The conductor shielding layer and the insulating rubber layer are sequentially coated on the outside of the conductor core, and finally the EVA material is wrapped around the outside of the insulating rubber layer to form an outer sheath layer to obtain an anti-corrosion cable.
Citation Information
Patent Citations
Aging-resistant material for electric wires and preparation method
CN107236184A
Long-acting graphene antiseptic primer and preparation method thereof
CN107418389A
Flame-retardant cable and preparation method thereof
CN113831630A